2006
DOI: 10.1177/1043659606288372
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Health Behavior Theories Applied to Breast-Screening Behavior for Relevance With American Indian Women

Abstract: This article reviews studies of the efficacy of breast-screening interventions and their related theories that have had a positive effect in influencing women to use mammography and assesses the potential of various behavioral models for use with American Indian women. The study involved a search of literature in nursing and other health fields. Both community and practice-based interventions have incorporated elements of various theoretical models. Because of its adaptability, the modified health behavior mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…For instance, family, spouses, and community support all played important roles in motivating women to participate in early breast cancer screening, and enabled adherence to clinical appointments. These findings can be used to promote transcultural nursing training about the importance of working with tribal communities in context of their interconnected relations and social networks (Becker & Foxall, 2006; Haozous, Eschiti, Lauderdale, Hill, & Amos, 2010; Weiner, Burhansstipanov, Krebs, & Restivo, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, family, spouses, and community support all played important roles in motivating women to participate in early breast cancer screening, and enabled adherence to clinical appointments. These findings can be used to promote transcultural nursing training about the importance of working with tribal communities in context of their interconnected relations and social networks (Becker & Foxall, 2006; Haozous, Eschiti, Lauderdale, Hill, & Amos, 2010; Weiner, Burhansstipanov, Krebs, & Restivo, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Barriers to routine mammography that have been identified in studies with AIs include lack of access to mammography due to cost and lack of transportation, fear of being diagnosed with breast cancer, mistrust of mainstream healthcare establishments and the feeling of embarrassment during the mammogram test (Daley et al, 2012; Watson-Johnson et al, 2011). Practice-based mammography interventions such as sending reminders or telephone counseling have not been effective with the AI population because of migratory patterns and cultural factors (Becker & Foxall, 2006). To improve screening rates for AIs, interventions should be culturally tailored, and factors such as facility barriers within healthcare systems, tribal-specific information, role of family, and women's opinions about screening tests should be considered when planning breast screening interventions with AI communities (Becker & Foxall, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Practice-based mammography interventions such as sending reminders or telephone counseling have not been effective with the AI population because of migratory patterns and cultural factors (Becker & Foxall, 2006). To improve screening rates for AIs, interventions should be culturally tailored, and factors such as facility barriers within healthcare systems, tribal-specific information, role of family, and women's opinions about screening tests should be considered when planning breast screening interventions with AI communities (Becker & Foxall, 2006). It is important to consider some of these factors as screening rates among AIs have been shown to vary with tribal affiliation and geographical location (Roubidoux, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reporting by tribe would greatly increase the ability to plan local collaborations designed to improve the health of these populations. For instance, an analysis by Becker and Foxall of health behavior theories applied to breast screening behavior in AI women found that the most effective interventions were those that were theory-driven, were adaptable, and emphasized a tribal community–researcher partnership (24). …”
Section: Discussionmentioning
confidence: 99%